Phase equilibria in metastable regime in the (C8H12NO)2[ZnCl4] ferroelectric system. Issue 5 (18th January 2018) - Mezzadri, F.; Mahbouli Rhouma, N.; Delmonte, D.; Cabassi, R.; Loukil, M.; Calestani, G.
Abstract : (C8 H12 NO)2 [ZnCl4 ] is a hybrid organic–inorganic compound displaying ferroelectric properties and polymorphism, with phase transitions taking place in the metastable regime. Abstract : (C8 H12 NO)2 [ZnCl4 ] is an interesting ferroelectric organic–inorganic hybrid compound that shows a complex structural phase diagram, investigated in this work by X-ray diffraction and differential scanning calorimetry, characterized by an irreversible transition occurring on heating at 390 K, and coupled with successive transformations taking place on cooling in a metastable regime. The basic structural transition, leading from a monoclinic P 21 to an orthorhombic P 21 21 21 symmetry and involving the doubling of the unit cell volume, is associated with an order–disorder transformation of the 4-methoxybenzylammonium cations coupled with a reorientation of tetrachloridozincate anions. During cooling, the cationic order and the monoclinic symmetry are progressively restored, but the doubling of the original cell volume is maintained by the alternate canting of adjacent cationic layers. It is noteworthy that all the polymorphs preserve the non-centric nature of the structure, but the ferroelectric behavior, characterized by high saturation polarization P S = 17 μC cm −2 and relatively low coercive field E C = 8 kV cm −1, is lost in the transition on heating and not recovered at low temperature when the original polar P 21 symmetry is restored.